Optimizing 4G LTE radio coverage areas with an outdoor extender booster - MUKANDA LUKENGO , Papy; BOPE SAIDI , Médard Arnauld; TSHIKUDI TSHIKUDI , Dennis; TSHINYAM KAPEND , Franck (Revue Internationale du Chercheur, 2024)
Nowadays with the multitude of networked mobile services, networked communications have become indispensable, wherever the cell phone is located （Dcs，2013）. However, in some areas, phone calls and internet services are poor and sometimes unavailable, especially for 4G LTE services. In practice, 4G LTE service is not yet stable in DR Congo, and some areas do not reach the 4G LTE signal. This is because the 4G signal is easily attenuated by surrounding conditions, such as the presence of tall buildings, trees and so on. To solve this problem, we have proposed a solution, to have a 4G Outdoor extension antenna that operates on the 825 MHz - 875 MHz frequency bands, with a good reflectance to provide additional 4G LTE signal coverage. The basis of this study is to increase the coverage of areas that do not receive the 4G LTE signal, and areas with very poor 4G radio conditions located at a great distance from the 4G base station to such an extent that every cell phone can receive signals without having any disturbance.